Ameliorated Full-Endoscopic Transforaminal Decompression for L5–S1 Foraminal and Extraforaminal Stenosis. Issue 6 (July 2021) - Yang, Chang-Chen; Yeh, Kuang-Ting; Liu, Keng-Chang; Wu, Wen-Tien
Abstract : Study Design: This is a retrospective review. Objective: To describe a modified surgical technique, full-endoscopic transforaminal decompression (FETD) in patients with L5–S1 foraminal stenosis or extraforaminal stenosis (EFS) and to detail the short-term results. Summary of Background Data: Performing FETD surgery for L5–S1 FS and EFS is challenging because of high iliac crests in most cases and the difficulty in accurately differentiating between FS and EFS by images preoperatively. Material and Methods: Patients who had solitary unilateral L5–S1 FS or EFS and had undergone FETD between October 2014 and December 2017 were included. In total, 22 patients underwent FETD for L5 root compressions at the L5–S1 levels. All patients were followed up for more than 1 year. Results: The mean visual analog scale score for back and leg pain, assessed preoperatively and at 12 months postoperatively, improved from 6.3±1.7 to 1.59±1.30 and from 7.29±0.78 to 1.41±1.20, respectively. The mean Oswestry Disability Index improved from 61.53% preoperatively to 15.8% at 12 months postoperatively. Neurovascular injury–related complications were absent in all these cases. Conclusion: Successful short-term clinical outcome is achievable using the ameliorated FETD technique for treating L5–S1 FS and EFS. Abstract : Supplemental Digital Content is available in the text.